Physical variables - lake temperature profile from Stortjärn, platform - Svartberget Research Station (Swedish University of Agricultural Sciences, 2023)
High frequency temperature profiles are measured in lakes of SITES Water to be able to determine the thermal structure.
Svartberget Research Station (2023). Physical variables - lake temperature profile from Stortjärn, platform, 2016-07-02–2023-09-08 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/aFLYKLWP5yvZgMYVhTVrs0wy
Keywords: SITES; Time instant; Time instant; Water temperature; Water temperature; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap